2020
DOI: 10.1002/marc.202000597
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects Control Spiropyran–Merocyanine Equilibria and Mechanochromic Utility

Abstract: From a microscopic point of view, CC bond cleavage produces radicals which may undergo secondary reactions that further destabilize polymeric materials. Thus, for a long time, such mechanicallyinduced bond scission and degradation has been treated in negative context, as these reactions occurred in an uncontrolled way, at undefined positions at the polymer chain and usually caused property profiles of lower quality. The view on mechanically-induced chemical reactions has meanwhile changed, with mechanochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…15 Further, the mechanochromic properties of spiropyran could be tuned by inserting suitable substituents to the mechanophores. 16 These studies have shown that even subtle differences between reactants can affect how mechanical stress activates chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Further, the mechanochromic properties of spiropyran could be tuned by inserting suitable substituents to the mechanophores. 16 These studies have shown that even subtle differences between reactants can affect how mechanical stress activates chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 , 33 ] Craig and coworkers have demonstrated that the force required for the isomerization of spiropyran can be tuned by varying the attachment points of the OFP to the polymer chain. [ 34 , 35 ] However, this has only a minimal effect on the mechanical activation in bulk polymeric materials due to the elusive nature of the interplay between molecular OFP and macroscopic polymer system. [ 36 , 37 ]…”
Section: Tailoring the Force Rangementioning
confidence: 99%
“…Extensive reports about the theory and application of such systems can be found in refs. [165][166][167][168]. One of the most investigated mechanochromic species is spiropyran (SP).…”
Section: From Cromatophore As Absorbance Elements Through Molecular Mechanochromic Devicesmentioning
confidence: 99%